Large enhancement of the anomalous Hall effect in Co/Pt multilayers sandwiched by MgO layers - Zhang, S; Teng, J; Zhang, J; Liu, Y; Li, J; Yu, G; Wang, S (American Institute of Physics, 2010)
We report a large enhanced anomalous Hall effect (AHE) in the Co/Pt multilayers sandwiched by two MgO layers. The Hall resistivity ([rho]xy) was over an order of magnitude larger than that in pure Co/Pt multilayers. By optimizing the thickness of MgO layers, a high field sensitivity value of 2445 V/A T for Hall sensors was achieved. The enhancement of AHE is mainly attributed to the MgO-Pt interfacial effect.